Evolving roles of cross-sectional imaging in Crohn's disease. Issue 9 (September 2016) - Magarotto, Andrea; Orlando, Stefania; Coletta, Marina; Conte, Dario; Fraquelli, Mirella; Caprioli, Flavio
Abstract: The implementation of cross-sectional imaging techniques for the clinical management of Crohn's disease patients has steadily grown over the recent years, thanks to a series of technological advances, including the evolution of contrast media for magnetic resonance, computed tomography and bowel ultrasound. This has resulted in a continuous improvement of diagnostic accuracy and capability to detect Crohn's disease-related complications. Additionally, a progressive widening of indications for cross-sectional imaging in Crohn's disease has been put forward, thus leading to hypothesize that in the near future imaging techniques can increasingly complement endoscopy in most clinical settings, including the grading of disease activity and the assessment of mucosal healing or Crohn's disease post-surgical recurrence.